Reference indexes of the goat milk price - Camúñez J.A.; Morales E.; Ruíz F.A.; Mena Y. (Innovation for sustainability in sheep and goats, 2019)
According to the current EU legislation, all transactions of raw milk that take place in Spain should be registered in a contract. This contract must reflect, among other aspects, the price of milk, which can be fixed or variable. In case of being variable, it must be indicated on the basis of which that price will vary. Conscious of the importance of the reference used, the INLAC (Spanish Inter-professional of Milk) has made available to the sector some price indexes that serve as a reference for the contract. These indexes have been developed by the authors of this paper, which guarantees its transparency and impartiality. Based on interviews taking to traders and experts and using econometric adjustment methods (in which autoregressive techniques are involved), two indexes are proposed, both referring to the price of the total Useful Dry Matter content (protein plus fat): Index nº 1, reflecting the variation of market prices, and the Index nº 2 which also incorporates two factors regarding to the international market. A case-study shows a good adjustment between the real evolution of the prices and the behavior of the indexes.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)